(untitled) (Asian Journal of Medical and Biological Research, 2017)
Study was conducted to identify the changes in nutritional and microbiological aspects of fresh, smoked, salt-smoke-dried (SSD: treated with salt, smoke and sunlight), Control dried (CD: treated only with sunlight) tengra (Mystus tengara) during storage at ambient temperature (26-28oC) and refrigeration temperature (40C). The study was done to investigate the effect of natural preservatives salt and smoke on the shelf life of the product over the storage period. The moisture content of fresh tengra was 76.06% whereas 18.80 and 18.36% for SSD and CD respectively. Fresh tengra had 13.45% protein, 7.46% lipid and 2.80% ash. The initial value of protein, fat and ash content of SSD tengra was 63.40, 19.95 and 16.55% respectively on dry matter basis. During 60 days storage period moisture increased whereas protein, fat, and ash content decreased considerably. After two month storage at ambient temperature the protein, lipid and ash content for SSD tengra were 62.75, 19.07 and 15.99% respectively whereas the values of the same parameters stored at refrigeration temperature were 62.54, 19.54 and 16.12% respectively on dry matter basis. The initial TVB-N and SPC value for SSD tengra was 5.86 mg/100g and 1.02×104 CFU/g respectively. During storage period the TVB-N and SPC value slowly increased and the values reached to 18.21 mg/100g and 3.32×104 CFU/g respectively for salt-smokedried tengra stored at ambient condition whereas 11.81mg/100g and 2.14×104 CFU/g respectively for the products stored at refrigeration temperature. The overall quality of salt-smoke-dried product was better than control dried product on the basis of organoleptic, nutritional and microbial aspects. Information obtained from this study it is cleared that, combination of salting, smoking and drying is efficient method of fish processing which could be useful to consumers, processors, and nutritionist at national and global basis. Asian J. Med. Biol. Res. December 2016, 2(4): 678-684